2018
DOI: 10.1007/s11571-017-9471-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of evodiamine in experimental paradigm of Alzheimer’s disease

Abstract: Evodiamine, a major component of , has been reported to possess various pharmacological activities, including anti-inflammatory, antioxidative stress, and neuroprotective effects. Our previous study has shown that the potential effects of evodiamine on the learning and memory impairments in the transgenic mouse model of Alzheimer's disease (AD). The present study was designed to investigate neuroprotective mechanism and therapeutic potential of evodiamine against intracerebroventricular streptozotocin (ICV-STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…The team of Yuan used SAMP8 and APPswe/PS1ΔE9 transgenic mice with doses of 50 mg/kg/day and 100 mg/kg/day to evaluate the pharmacological efficacy of Evo [92]. The results of the behavioral tests were consistent with those of Wang [88], and higher doses showed better improvement. Western blotting analysis revealed that Evo significantly reduced the accumulation of COX-2 protein, which is one of the important determinants of inflammatory response-mediated cytotoxicity.…”
Section: Evodiaminementioning
confidence: 79%
See 1 more Smart Citation
“…The team of Yuan used SAMP8 and APPswe/PS1ΔE9 transgenic mice with doses of 50 mg/kg/day and 100 mg/kg/day to evaluate the pharmacological efficacy of Evo [92]. The results of the behavioral tests were consistent with those of Wang [88], and higher doses showed better improvement. Western blotting analysis revealed that Evo significantly reduced the accumulation of COX-2 protein, which is one of the important determinants of inflammatory response-mediated cytotoxicity.…”
Section: Evodiaminementioning
confidence: 79%
“…In recent years, scholars have gradually begun to apply it to the treatment of AD. Wang et al performed intragastric administration of intraventricular streptozotocin-induced C57BL/6 mice with Evo for 21 days at 50 mg/kg/day and 100 mg/kg/day [88]. The effect of 100 mg/kg of Evo in mice was similar to that of the positive control group, donepezil-treated mice.…”
Section: Evodiaminementioning
confidence: 97%
“…Evodiamine (Evo) is a quinozole alkaloid that is mainly isolated from the fruits of Evodia rutaecarpa . In recent studies, Evo showed good anti‐inflammatory activity by inducing protective effects on kidney ischaemia reperfusion injury in rats, an experimental model of Alzheimer's disease and dextran sulfate sodium‐induced experimental colitis in mice . In vitro , Evo has also been proven to inhibit the function of active immune cells and decrease pro‐inflammatory cytokine secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the content of phosphorylated and non-phosphorylated NMDAR subunits in the hippocampus of AD patients are reduced (Sze et al, 2001). Consistently, in SAMP8 mice or AD models injected with Aβ 25-35 or Aβ 1-42 , the expression of NMDAR1, NMDAR2A and NMDAR2B were decreased markedly in the hippocampus or cortex (K. W. Chang et al, 2020; K. Wang et al, 2018; Xu et al, 2016). Moreover, it has been demonstrated that ketamine, a noncompetitive NMDAR antagonist, could ameliorate the impaired learning and memory of developing mice induced by repetitive mechanical stress, and the mechanism may be associated with the increased hippocampal BDNF expression (C. H. Chang, Su, & Gean, 2018; Peng, Zhang, Wang, Ren, & Zhang, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…New object recognition index, a ratio of the amount of time spent exploring the novel object over the total time spent exploring the both, was used to evaluate cognitive function. A mouse was scored as exploring the object when touching or sniffing the object with its nose or front legs, and facing the object at a distance within 1 cm (D. Wang, Wang, Liu, & Li, 2018).…”
Section: Methodsmentioning
confidence: 99%